2017
DOI: 10.1172/jci92885
|View full text |Cite
|
Sign up to set email alerts
|

Androgen-mediated sex bias impairs efficiency of leukotriene biosynthesis inhibitors in males

Abstract: Proinflammatory leukotrienes (LTs) are produced by 5-lipoxygenase (5-LO) aided by 5-LO-activating protein (FLAP). LT biosynthesis inhibitors are currently under clinical investigation as treatments for respiratory and cardiovascular diseases. Here, we have revealed a sex bias in the efficiency of clinically relevant LT biosynthesis inhibitors, showing that their effects are superior in females. We found that androgens cause these sex differences by impeding the LT-biosynthetic 5-LO/FLAP complex assembly. Lower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
72
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(84 citation statements)
references
References 55 publications
3
72
0
1
Order By: Relevance
“…Regarding the differential expression of SPM‐biosynthetic enzymes, our results are consistent with previous studies that show that the activity of 5‐LOX and 12/15‐LOX are influenced by sex hormones 62,63 . Moreover, we observed an SS‐dependent difference in the expression of 5‐LOX and 12/15‐LOX between female NOD/ShiLtJ mice after disease onset as compared their young counterparts.…”
Section: Discussionsupporting
confidence: 91%
“…Regarding the differential expression of SPM‐biosynthetic enzymes, our results are consistent with previous studies that show that the activity of 5‐LOX and 12/15‐LOX are influenced by sex hormones 62,63 . Moreover, we observed an SS‐dependent difference in the expression of 5‐LOX and 12/15‐LOX between female NOD/ShiLtJ mice after disease onset as compared their young counterparts.…”
Section: Discussionsupporting
confidence: 91%
“…The sample size for experiments was chosen empirically based on previous studies (12,20) to ensure adequate statistical power.…”
Section: Resultsmentioning
confidence: 99%
“…The results open a new area study; that is, investigating differences in fatty acid and SPM metabolism between sexes in the context of obesity, which could have strong implications for the use of drugs that target PUFA metabolic pathways. For instance, Pace et al., recently demonstrated that females are more responsive to leukotriene biosynthesis inhibitors than males due to differences in androgens between sexes . Similarly, there are data to show that female humans are protected from inflammation induced endothelial impairments due to elevated levels of specific SPMs …”
Section: Discussionmentioning
confidence: 99%
“…For instance, Pace et al, recently demonstrated that females are more responsive to leukotriene biosynthesis inhibitors than males due to differences in androgens between sexes. 74 Similarly, there are data to show that female humans are protected from inflammation induced endothelial impairments due to elevated levels of specific SPMs. 75 The males and females had different metabolic profiles, which would influence the levels of SPM precursors.…”
Section: Discussionmentioning
confidence: 99%